Analysis of Convergence and the Scenarios of Economic Growth in Indonesia Using System Dynamic Approach - Zulita, Nur Avia; Prianto, Fajar Wahyu; Riniati, Riniati; Wiryaningtyas, Dwi Perwitasari (Gorontalo Development Review, 2024)
This study aims to determine whether there is sigma convergence and beta convergence in Indonesia, to determine the effect of electricity infrastructure, human development, and ICT on convergence of economic growth, and to determine the scenario that can accelerate economic growth in Indonesia. The data used in this study is secondary data. The methods used are convergence analysis, panel data regression analysis, and dynamic system approach. The results showed that there was sigma convergence and no beta convergence in Indonesia in 2013-2022. Electricity infrastructure, human development, and ICT have not been able to encourage convergence of economic growth with electricity infrastructure having a significant negative effect, human development having a significant positive effect, and ICT having an insignificant negative effect. Scenarios that can be done to accelerate economic growth are structural scenarios and parameter scenarios.